2012
DOI: 10.1542/peds.2011-3029
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Vitamin D Supplementation and Risk of Acute Respiratory Infection in Mongolia

Abstract: Vitamin D supplementation significantly reduced the risk of ARIs in winter among Mongolian children with vitamin D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
220
2
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(240 citation statements)
references
References 24 publications
7
220
2
11
Order By: Relevance
“…One trial of Mongolian children with profound vitamin D deficiency (17.5 nmol/L) found a reduction of 0.35 respiratory tract infections over 3 months. 38 …”
Section: Belief 3: Vitamin D Reduces Respiratory Tract Infections Obsmentioning
confidence: 99%
“…One trial of Mongolian children with profound vitamin D deficiency (17.5 nmol/L) found a reduction of 0.35 respiratory tract infections over 3 months. 38 …”
Section: Belief 3: Vitamin D Reduces Respiratory Tract Infections Obsmentioning
confidence: 99%
“…In addition, supplementation with vitamin D can prevent seasonal influenza 13 and acute respiratory infections in children. 39 An investigation 40 based on data from the National Hospital Discharge Survey showed that the seasonal incidence of sepsis increased 16.5% in the winter (P < .05), especially sepsis due to respiratory infections. Although 25-hydroxyvitamin D levels were not assessed in that study, 40 vitamin D deficiency through decreased sun exposure in winter months may play a role.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…2. People who do not supplement may expect to have greater susceptibility to infectious diseases such as tuberculosis (39) and viruses (40)(41)(42) , which have been shown to respond to vitamin D supplementation in clinical trials through improved innate immunity, with increased production of cathelicidin and other natural bacteriocides. 3.…”
Section: Harms Consequent Upon False Inference Of Reverse Causationmentioning
confidence: 99%